KEEFEKTIFAN CERITA UNTUK MENANAMKAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR - Chairiyah Chairiyah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstract: This study aims to (1) examine the effectiveness of the story to name character education which is focused on the value of devotion of worship, honesty, responsibility, and caring (2) to test the effectiveness of the story to improve cognitive learning outcomes in social studies. This research is a quasi experimental research with pre-test and post-test control group design. The independent variable in this research is the social studies learning method by reading the story. The dependent variable is the result of social studies learning and character values. The moderator variable is the personality type (introvert and extrovert). This research was conducted in class V SDN Nanggulan I Kulonprogo as experimental group and class V SDN Jatisarono Kulonprogo as control group. The subjects of this study were all students obtained by test and non-test. Data were analyzed using descriptive statistics and inferential statistics with MANOVA (Multivariate Analysis of Variance) at 95% significance level (p = 0,05). The results showed thatÂ  there were significant differences in social studies learning outcomes and student character values between the experimental class and control class. In the experimental class, social studies score increased by 2.94 (11.53%), 1.88 (5.66%), honesty 1.19 (5.66%), responsibility 3,57 (9.83%), concern for 1.58 (9.55%). In the control class, the score of social studies learning achievement was 0.95 (3.75%), 0.09 (0.34%) observance, honesty 2.39 (12.38%), responsibility 0.09 (0, 25%), concern 0.09 (0.55%). From the comparison, it can be concluded that the increase of IPS learning result score and student character values in the experimental class is higher than the control class. In other words, the use of effective stories to improve social studies learning outcomes and character values.